2021
DOI: 10.1109/access.2021.3107294
|View full text |Cite
|
Sign up to set email alerts
|

Pixel and Object-Based Machine Learning Classification Schemes for Lithological Mapping Enhancement of Semi-Arid Regions Using Sentinel-2A Imagery: A Case Study of the Southern Moroccan Meseta

Abstract: Mapping lithological units of an area using remote sensing data can be broadly grouped into pixel-based (PBIA), sub-pixel based (SPBIA) and object-based (GEOBIA) image analysis approaches. Since it is not only the datasets adequacy but also the correct classification selection that influences the lithological mapping. This research is intended to analyze and evaluate the efficiency of these three approaches for lithological mapping in semi-arid areas, by using Sentinel-2A data and many algorithms for image enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 79 publications
1
7
0
Order By: Relevance
“…Unlike the majority of previous studies that adopted individual MLAs using thirdparty software for lithological mapping of small geographical areas [3,4,13,[126][127][128][129], we exploit the capabilities of the GEE cloud computing platform to perform the MLAs procedure using the spatio-spectral data from Sentinel 2. The spatial information was used as a pixel local variability in band measurements (entropy and contrast) contained in the texture index images extracted from the GLCMs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Unlike the majority of previous studies that adopted individual MLAs using thirdparty software for lithological mapping of small geographical areas [3,4,13,[126][127][128][129], we exploit the capabilities of the GEE cloud computing platform to perform the MLAs procedure using the spatio-spectral data from Sentinel 2. The spatial information was used as a pixel local variability in band measurements (entropy and contrast) contained in the texture index images extracted from the GLCMs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the SVM has advantages in terms of small samples and high dimensionality [104]. However, the fast performance and accurate results make SVM one of the widely used lithological mapping classifiers [4,105].…”
Section: Support Vector Machine (Svm)mentioning
confidence: 99%
See 3 more Smart Citations